Correlation of self-efficacy and interest in learning with Indonesian Language learning achievement of class X students MAN 1 Kendari - Ana, Haerun; Udu, Sumiman; Saidiman, Saidiman (ARKA INSTITUTE, 2024)
This study aims to determine whether or not there is a relationship between self-efficacy and interest in learning with Indonesian Language learning achievement of grade X students of MAN 1 Kendari. This research is a correlational research with quantitative method. The population consisted of 417 students with a sample of 80 students. Data were collected through questionnaires for self-efficacy and interest in learning variables, and documentation for Indonesian Language learning achievement variables. The results of this study indicate that there is a correlation between self-efficacy and Indonesian Language learning achievement in class X students of MAN 1 Kendari. The strength of the correlation is in the medium category, with a positive direction and statistically significant. In addition, there is a correlation between learning interest and Indonesian Language learning achievement in the same students, with a strong correlation strength level, positive direction, and statistically significant. Simultaneously, self-efficacy and interest in learning also show a strong correlation, with a positive direction and statistically significant to Indonesian Language learning achievement of grade X students of MAN 1 Kendari. Therefore, optimizing self-efficacy and interest in learning can contribute to improving students' Indonesian Language learning achievement.